AI Chatbot for College Enquiry - Rashmi Tiwari; Reema Khandelwal; Yash Agrawal; Vinit Tiwari; Wani H. Bisen (International Journal of Engineering and Management Research, 2023)
Every campus needs a campus guide to answer different types of questions without any problem. Every newly enrolled student in the college has a long list of queries- “What are college timings”, “Where is the gym?”, “When does the library open?”, etc. Further, students have queries regarding syllabus, academic calendar, semester break and so on and so forth. To tackle these problems we are incorporating Artificial Intelligence(AI) technology which is spreading wide across all the fields, and reduces the time and efforts of humans by providing optimized results. So, we are going to implement a virtual assistant using artificial intelligence techniques and natural language processing that can solve any college related query. This will function as a machine with Artificial based intelligence. Machine learning algorithms will be used to train the bot, and once trained on a large enough dataset, the bot will understand college-related inquiries. The bot also understands the intent and meaning behind the orders. The AI chatbot identifies the input, context, and intent, which then reacts accordingly.